Elevated intracranial pressure, low cerebral perfusion pressure, and impaired brain metabolism correlate with fatal outcome after severe brain injury - Hejčl, A; Bolcha, M; Procházka, J; Hušková, E; Sameš, M (Journal of neurological surgery. Part A, Central European neurosurgery, 2012)
BACKGROUND: New brain tissue monitoring techniques (tissue oxymetry, microdialysis) provide direct information about the state of brain oxygenation and brain metabolism in patients with severe traumatic brain injury (TBI). Despite this information being limited to a small region of the brain surrounding the probes, it could be associated with such global parameters as the clinical outcome. OBJECTIVE: To study the predictive value of monitoring brain oxygenation and metabolism on clinical outcome in patients in the acute phase of severe TBI. METHODS: An observational study of 20 patients with a severe TBI was undertaken, utilizing intracranial pressure (ICP), cerebral perfusion pressure (CPP), brain tissue oxygenation, and brain metabolism monitoring. We correlated the clinical outcome of the patients with the following parameters: ICP, CPP, brain tissue oxymetry (PbtO2), glucose and glycerol levels, and the lactate/pyruvate (LP) ratio. Further, we analyzed the relationship between ICP, CPP, PbtO2, and the metabolism parameters. RESULTS: We found a correlation of the mean ICP values (8.73 ± 1.18 in group A vs. 26.32 ± 5.01 mmHg in group B, p < 0.005), the mean CPP values (84.82 ± 2.02 in group A vs. 66.62 ± 4.64 mmHg, p < 0.005), the LP ratio (37.36 ± 3.44 vs. 199 ± 87.97, p < 0.05), and glycerol levels (62.07 ± 12.14 vs. 215 ± 46.52 μmol/l, p < 0.05) with the clinical outcome. High ICP correlated with both a high LP ratio (Spearman R = 0.61, p < 0.05), and elevated glycerol concentrations (Spearman R = 0.48, p < 0.05). A low CPP correlated with a high LP ratio (Spearman R = -0.57, p < 0.05), while a low PbtO2 correlated with a high LP ratio (Spearman R = -0.49, p < 0.05). CONCLUSIONS: High ICP, low CPP, an elevated mean LP ratio, and high glycerol concentrations in the acute phase predict fatal outcome 6 months after TBI. Further, high ICP, low CPP, and low PbtO2 correlate with impaired brain metabolism.
Keywords: Young Adult; Male; Cerebrovascular Circulation; mladý dospělý; Adolescent; Brain; mozkový krevní oběh; prognóza; poranění mozku; Brain Injuries; intrakraniální hypertenze; Adult; dospělí; mužské pohlaví; Intracranial Hypertension; mladiství; lidé; ženské pohlaví; Humans; mozek; Prognosis; Female; lidé středního věku; Middle Aged